2013
DOI: 10.1186/1758-5996-5-27
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training decreases 24-hour blood pressure in women with metabolic syndrome

Abstract: BackgroundThe purpose of this study was to verify the effects of eight weeks of resistance training (RT) on 24 hour blood pressure (BP) in patients with and without metabolic syndrome (MetS).MethodsSeventeen women volunteered to participate in this study, 9 with MetS (37.0 ± 8.7 yrs; body mass 77.3 ± 9.7 kg; body mass index 30.3 ± 4.2 kg · m-2) and 8 without MetS (35.1 ± 7.2 yrs; body mass 61.3 ± 8.1 kg; body mass index 24.2 ± 2.5 kg · m-2). Individuals were subjected to eight weeks (3 times/week) of whole bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
2
18
0
4
Order By: Relevance
“…For example, Tibana et al [20] found that an acute submaximal RE session was effective in decreasing SBP, DBP and MBP during 24 h and throughout nighttime hours in overweight/obese middle-aged women [8]. In a chronic study, Strasser et al [19] found a significant reduction of mean BP measured during 24 h after a 4-month RE program in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tibana et al [20] found that an acute submaximal RE session was effective in decreasing SBP, DBP and MBP during 24 h and throughout nighttime hours in overweight/obese middle-aged women [8]. In a chronic study, Strasser et al [19] found a significant reduction of mean BP measured during 24 h after a 4-month RE program in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that both SBP and DBP decreased in the nighttime period ( − 4.2 mmHg and − 4.1 mmHg, respectively) and in the overall 24 h period ( − 3.6 mmHg and − 4.5 mmHg, respectively) following the acute RT session compared to the control trial. In addition, Tibana et al [ 33 ] analysed the eff ects of 8 weeks of RT program (3 sets with 8-12 RM, 3 times per week of whole body RT) on 24 h BP in 17 adult women with (n = 9) and without metabolic syndrome (n = 8). The authors found decreased mean and diastolic night-time BP ( − 3.9 mmHg, p = 0.04; − 5.5 mmHg, p = 0.03, respectively) after 8 weeks of RT only in middle-aged women with metabolic syndrome.…”
mentioning
confidence: 99%
“…Acute bouts of resistance exercise may also provide modifi cations on blood pressure [ 10 , 35 , 40 ] . De Souza et al (2013) and Tibana et al (2013) suggested that RET may be a useful modality to reduce blood pressure in women. Data from Queiroz et al (2103) also suggest that this response is similar in men.…”
mentioning
confidence: 99%